Event Structure Semantics for Dynamic Graph Grammars - Bruni, Roberto; Melgratti, Hernan; Montanari, Ugo (Electronic Communications of the EASST, 2007)
Dynamic graph grammars (DGGs) are a reflexive extension of Graph Grammars that have been introduced to represent mobile reflexive systems and calculi at a convenient level of abstraction. Persistent graph grammars (PGGs) are a class of graph grammars that admits a fully satisfactory concurrent semantics thanks to the fact that all so-called asymmetric conflicts (between items that are read by some productions and consumed by other) are avoided. In this paper we introduce a slight variant of DGGs, called persistent dynamic graph grammars (PDGGs), that can be encoded in PGGs preserving concurrency. Finally, PDGGs are exploited to define a concurrent semantics for the Join calculus enriched with persistent messaging (if preferred, the latter can be naively seen as dynamic nets with read arcs).